Framing Madame B: Quotation and Indistinction in Mieke Bal and Michelle Williams Gamaker’s Video Installation - Filipczak, Dorota (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The article engages with the video installation Madame B by Mieke Bal and Michelle Williams Gamaker. The work was premiered in the city of Łódź in Poland (between 6 Dec. 2013 and 9 Feb. 2014). The author makes use of the exhibition brochure by two artists published by the Museum of Modern Art, and the recording of a seminar held by Bal and Williams Gamaker after launching their work. The article focuses on the innovative audiovisual interpretation of Flaubert’s famous novel. Basing the argument on the concept of framing created by Bal, the author applies it to Bal and Williams Gamaker’s exhibition by relating it to the history and culture of the Polish location where it was first shown. Above all, however, the article discusses the importance of quotation and indistinction in Madame B, where the artists quote from (among others): Louise Bourgeois, Maya Deren, Artemisia Gentileschi, Charlotte Perkins Gilman, William Kentridge and Sol LeWitt.